Anticancer Effects of Baicalein on Hepatocellular Carcinoma Cells. (4th March 2014) - Zheng, Yi‐Hu; Yin, Li‐Hui; Grahn, Tan Hooi Min; Ye, Ai‐Fang; Zhao, Yan‐Rong; Zhang, Qi‐Yu
<x xml:space="preserve">Abstract</x> The therapeutic potential of baicalein against hepatoma cells was evaluated in vitro and in vivo. In cell viability assays, baicalein showed significant cytotoxicity against the hepatocellular carcinoma cell lines H22, Bel‐7404, and Hep G2 and moderate cytotoxicity against immortalized human hepatocytes. Baicalein induced G0/G1‐phase arrest in hepatocellular carcinoma cells, inhibited AKT, and promoted the degradation of β‐catenin and cyclin D1 without activation of GSK‐3β. Furthermore, baicalein significantly inhibited H22 xenograft tumor growth without causing obvious adverse effects on weight or liver and spleen weight indexes in ICR mice. Immunohistochemical analysis showed that the inhibition of tumor growth in baicalein‐treated mice was associated with decreased AKT, β‐catenin, and cyclin D1 expression ex vivo. Our data indicate that baicalein might regulate cyclin D1 transcription via a β‐catenin‐dependent mechanism, leading to cell cycle arrest at G0/G1 phase and impaired cancer cell proliferation. These results suggest that baicalein is a potential candidate for the treatment of hepatocellular carcinoma. Copyright © 2014 John Wiley & Sons, Ltd.